Actitudes, estilos de enseñanza y evaluación del aprendizaje - Quispe-Ayala, Cesar; Antezana, Régulo; Oré, Rosario; Salvatierra-Zambrano, Salvador (2023)
This book is an adaptation of an investigation presented to the Enrique Guzmán y Valle National University, which sought to study the relationship between teaching styles and attitudes towards the evaluation of learning in Primary Education Teachers of the UGEL 07 Santiago de Surco (Peru). A descriptive correlational investigation was applied, a sample of 132 primary education teachers from educational institutions of UGEL 07 was selected. The Teacher Teaching Styles Questionnaire, TSQT (Thinking Styles Questionnaire For Teacher), of Grigorenko and Sternberg (1992) and the scale of attitudes of teachers towards the evaluation of student learning, built by Zaragoza (2003). The statistical analysis of the data obtained allows us to reach the following conclusion: There is a statistically significant relationship between teaching styles and attitudes towards the evaluation of learning in primary education teachers of the UGEL 07 Santiago de Surco.
Keywords: attitudes; learning assessment; primary school teachers; teaching styles